Evaluation of Student Satisfaction with Computer Laboratory Facilities at UIN Sumatera Utara Using the C5.0 Algorithm - Rizky, Ishlahiyah Nur; Zufria, Ilka (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2025)
The evaluation of student satisfaction with the computer laboratory facilities at UIN Sumatera Utara is crucial for improving the quality of educational services provided by the institution. The main issue faced is the lack of accurate data regarding student satisfaction with the facilities available in the laboratory. This study aims to analyze the level of student satisfaction using the C5.0 algorithm, which is known for its effectiveness in data classification. The research methodology involves collecting data through a comprehensive survey covering various aspects of laboratory facilities, such as reliability, responsiveness, assurance, empathy, and tangibles. The survey was conducted with a number of students to obtain representative information about their satisfaction with the provided facilities. After data collection, data cleaning and processing steps were carried out to build a classification model using the C5.0 algorithm. The results of the study showed that the C5.0 model achieved a very high accuracy rate of 99.25%, with precision of 99.72% and recall of 99.45% on the training data. Meanwhile, on the testing data, the accuracy reached 97%, precision was 100%, and recall was 96%. These findings indicate that the model has a very high ability to accurately classify student satisfaction levels. In conclusion, this model can provide useful recommendations for the university to identify areas that need improvement to meet student expectations. The implication of this research is the importance of the continuous development of laboratory facilities to improve student satisfaction and create a more optimal learning experience